Studi Pengelolaan Air Limbah Industri Perkebunan Hortkultura PT Y untuk Aplikasi Tanah - Rizka Novembrianto; Adisty Regina (Prosiding ESEC, 2023)
Industrialization due to the increasing human population causes many positive impacts as well as negative impacts. PT Y is a small sample of industries that are trying to meet the increasing needs of society. PT Y is enganged in horticultural plantations with main commodities such as Cavendush bananas and several other commodities such as pineapples, avocados and others. From the fruit processing process, PT Y produces waste in the form of water used for washing fruit and domestic wastewater originating from employee sanitation which, if not managed properly, can have a negative impact on the environment in the form of environment pollution. The purpose of this study was to determine waste management and to implement an evaluation of PT Y’s liquid waste operating system for soil applications. This research includes literature research and data sources based on iterature studies and interviews with PT Y. The result of this study are that it can be concluded that PT Y has not met the standards for wastewater management for application to soil.